The Multinuclear NMR Approach. Contributions to the Chemistry of Platinum - Paul S. Pregosin (CHIMIA)
Applications of heavy atom nuclear magnetic resonance to problems in the chemistry of platinum are presented. The direct observation of the metal resonance is shown to be both technically feasible and scientifically valuable, often providing a unique picture of the solution chemistry. The question of linkage isomerism in platinum thiocyanate chemistry, a seemingly simple problem, is revealed to be rather complex, whereas investigating the interaction of tin(II) dichloride with platinum(II), a somewhat complicated area, can be made much simpler. The surprisingly large one-bond coupling constant (> 30,000 Hz) between tin and platinum is just one of a number spectroscopic curiosities associated with heavy metal NMR.